2009
DOI: 10.2353/jmoldx.2009.080100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of High-Resolution Melting Analysis as a Diagnostic Tool to Detect the BRAF V600E Mutation in Colorectal Tumors

Abstract: BRAF V600E is the predominantly occurring mutation of the cytoplasmic kinase BRAF , and , in colorectal cancer , its determination provides a diagnostic exclusion criterion for hereditary nonpolyposis colorectal cancer. The aim of our study was to develop a sensitive BRAF V600E high resolution melting (HRM) assay. We first established and optimized the BRAF HRM assay using a cell line dilution model , enabling us to detect 1% mutant DNA in a background of wild-type DNA. In a comparison , DNA sequencing and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
85
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 36 publications
4
85
2
2
Order By: Relevance
“…Results for dHPLC and HRM suggest that these techniques are adequately sensitive for detecting the mutation when present in ratios as low as 1% to 5% (of V600E allele in the background of WT allele). Pichler et al 6 obtained similar results performing HRM with reagents, real-time PCR equipment, and HRM analysis software (Roche Diagnostics, Vienna, Austria).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Results for dHPLC and HRM suggest that these techniques are adequately sensitive for detecting the mutation when present in ratios as low as 1% to 5% (of V600E allele in the background of WT allele). Pichler et al 6 obtained similar results performing HRM with reagents, real-time PCR equipment, and HRM analysis software (Roche Diagnostics, Vienna, Austria).…”
Section: Discussionmentioning
confidence: 76%
“…A possible explanation for this finding was given by Pichler et al, 6 who also observed a noticeable rate of false-positive cases with HRM and attributed it to the failure of Taq polymerase to recognize modified bases and, therefore, amplify more artifacts existing in DNA extracted from paraffin-embedded tissue than true mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst this enrichment technique results in high purity leukemia samples (>90%), in the context of a diagnostic molecular laboratory, a more cost-effective, rapid and less labor intensive method that is capable of high throughput is desirable. High resolution melting (HRM) analysis is a DNA mutation screening technique which is fast, relatively simple and has previously been shown to be a sensitive and reliable way of detecting the BRAF V600E mutation in tumor samples from patients with melanoma, 4 colorectal carcinoma 5 and, more recently, HCL. 6 Our aim was to determine the feasibility of using HRM analysis and subsequent SS to detect the BRAF V600E in DNA extracted from unenriched bone marrow aspirate and peripheral blood samples from patients with HCL.…”
Section: Introductionmentioning
confidence: 99%
“…We request that the authors comment on (1) the different melting behavior of the MCF-7 wildtype DNA and the SKMel28 DNA in the difference plots and (2) the failure to refer to other studies, 2 including their own work, 3 showing a detection limit of 5% mutated BRAF alleles using HRM in combination with conventional PCR.…”
mentioning
confidence: 99%